Perfil epidemiológico das infecções de corrente sanguínea causadas por leveduras do gênero Candida em dois hospitais terciários de Cuiabá/MT : 2006-2011 - Santos, Hugo Dias Hoffmann (2012)
Infections caused by Candida species are among the leading causes of bloodstream infections in hospitals and have high mortality rates. We conducted a cross-sectional study, laboratory-based and analysis of secondary data (medical records and other medical records) from January 2006 to December 2011 in two tertiary teaching hospitals in Cuiabá/MT. 130 episodes of candidemia in 124 patients showed clinical and microbiological confirmation of a total of 72,767 patients treated between. The prevalence of both hospitals candidemias was equal to 1.8 per 1,000 admissions cases, the death rate of 0.9 per 1000 admissions and lethality equal to 49.2%. Of the total patients, 58.5% belonged to the female and 41.5% were male. Of these, 61.5% were adults, 13.1% pediatric and 25.4% neonates. The intensive care units received 69.2% of patients. The average hospital stay for patients with candidemia was equal to 53.5 days (SD = 45.5, 95% CI = 45.6 to 61.4). The main risk exposures were: antifungals (85.4%), hospital stay ≥ 21 days (82.3%), central venous catheter (77.7%), H2 blockers (71.5%), parenteral nutrition (70.8%) and mechanical ventilation (63.8%). More antifungal agents were used: fluconazole (50.4%) and Amphotericin B (47.3%). Candida parapsilosis (38.5%), C. albicans (34.6%) and C. tropicalis (18.5%) were the most prevalent etiologic agents. Of the variables that were significant in univariate analysis, only central venous catheter, parenteral nutrition and age proved to be independent exhibitions (stepwise multivariate analysis) and also related to the outcome of death. By the same method, but evaluating the association between risk exposures and the isolated species, it was found that neutropenic patients contained higher chance episodes of candidemia by C. albicans (p=0.05; OR=2.4), it was also observed between sex and C. parapsilosis (p<0.01; OR=3.0) and parenteral nutrition, and C. tropicalis (p<0.05; OR=3.0). C. parapsilosis was more frequent in intensive care units in relation to C. albicans. The Candida yeasts for the non-albicans were the most prevalent (65.5%) in this population. The species C. parapsilosis emerged as the main etiologic agent of hematogenous infections caused by Candida species. The prevalence of candidemias observed in this study was similar to data published by other researchers in Brazil and other countries.